Geomorfologi Daerah Poduwoma dan Sekitarnya, Kecamatan Suwawa Timur, Kabupaten Bone Bolango - Ravit Tahaku; Fitryane Lihawa; Muhammad Kasim (-, 2026)
This study aims to identify the geomorphological conditions of Poduwoma and its surrounding areas, East Suwawa District, Bone Bolango Regency, through geological mapping at a scale of 1:10,000. Based on geomorphological analysis, the study area is divided into three main geomorphological units: the intrusive hill unit, the volcanic hill unit, and the fluvial floodplain unit. The drainage patterns are predominantly dendritic and parallel, reflecting relatively homogeneous lithological control and intensive erosional processes. Geologically, the study area is composed of two main lithological units, namely the diorite unit and the andesite unit. The diorite is characterized by a phaneritic texture with plagioclase, hornblende, biotite, and opaque minerals as its primary constituents, whereas the andesite exhibits aphanitic to porphyritic textures composed of plagioclase, hornblende, biotite, and a microcrystalline groundmass. Stratigraphic relationships indicate that the diorite represents the older rock unit, which was subsequently overlain by volcanic activity that produced the younger andesite unit. The results of this study indicate that the geological evolution of the area was controlled by volcanic arc magmatism, resulting in intermediate intrusive and extrusive rocks. The interaction between endogenous processes, particularly magmatism, and exogenous processes, mainly denudation, has produced the present-day hilly to mountainous landscape observed in the study area.